Athletic training and psychological predictors pf injury:a case study of Malaysian professional football players involved in Malaysian football league - Kumaraswamy, N; Singh, Rabindarjeet; Nor, Mohad Anizu Mohd (2002)
Sport psychology deals with many aspects, which are important in sports and games.Injury is one of the common things one can observe in most of the sport and games. Injuries occur either by accident or intentionally. There are many reasons one can think of injuries occurring and that psychological aspect is considered more important. Psychological predictors, psychological impacts, and psychological aspects of rehabilitation are vital to know. Therefore, the objective of the study is to determine psychological predictors leading to athletic injury with focusing to Malaysian football players involved in Malaysian Professional Football League. A descriptive method of research was used to determine the psychological predictors of injury among the selected state team players. A pilot study has been carried out to test the validity and reliability of the questionnaire. Cluster sampling was used to get the actual number of subjects. Based on this sampling method, all teams were clustered into five groups (North, South, East, West and East Malaysia). From these five groups, two teams from each cluster have randomly picked up as a subject (25 players each team x 10 teams = 250 players). Questionnaires, observation, and interview were the instruments that being used in determining psychological predictors of injury. For statistical analysis, Multiple Logistic Regression was used to identify the psychological predictors of injuries by using the Statistical Package for Social Science (SPSS) version 9.0 for windows. The results of this study has showed that most of the Malaysian professional football players scored higher in neuroticism, and lower in agreeableness and conscientiousness. The subjects were also found experiencing anxiety with poor self-esteem and mental toughness as well.